Answer:
g = -4 is the extraneous solution.
Explanation:
The given equation :
![(3)/((2g+8))=((g+2))/((g^(2)-16))](https://img.qammunity.org/2019/formulas/mathematics/college/zhl3n2206l8u86xswuc4zsbo430ebasm4w.png)
3 (g²-16) = ( g + 2 ) ( 2g + 8 )
3g² - 48 = 2g² + 8g + 4g + 16
( 3g² - 2g² ) = ( 8g + 4g ) + ( 16 + 48 )
g² = 12g + 64
g² - 12g - 64 = 0
g² - 16g + 4g - 64 = 0
g ( g- 16 ) + 4 ( g - 16 ) = 0
( g + 4 ) ( g - 16 ) = 0
Since ( g + 4 ) & ( g - 16 ) are zero factors
So, g = -4, 16
Now we test these solutions. for (g = -4)
L.H.S (Left Hand Side)=
![(3)/(2(-4)+16)=(3)/((-8+16))=-((3)/(8))](https://img.qammunity.org/2019/formulas/mathematics/college/qj7w19v0mzw3rd5ntb4xk3je1fs5tfwoth.png)
R.H.S. (Right Hand Side) =
![((g+2))/((g^(2)-16) )=(-4+2)/(16-16)=(2)/(0)](https://img.qammunity.org/2019/formulas/mathematics/college/9xkai7ks6tsriwmer40degbk42yadc0ybc.png)
L.H.S. ≠ R.H.S. So g = ( -4) is not the answer, so g = -4 is the extraneous solution.
Now for g = 16
L.H.S.
![((3)/(32+8))=(3)/(40)](https://img.qammunity.org/2019/formulas/mathematics/college/z61zksvscuxn0p59p3a2gdnzblqw55uf6g.png)
and R.H.S.
![(16+2)/(256-16)=(18)/(240)=(3)/(40)](https://img.qammunity.org/2019/formulas/mathematics/college/56a7i1sze9trhhmkjry8dhv6hk5gci5uby.png)
so LHS = RHS
Therefore. g = 16 is not the extraneous solution.